2017
DOI: 10.1038/s41598-017-07958-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of Dermcidin isoform-2 in the occurrence and severity of Diabetes

Abstract: Diabetes is now epidemic worldwide. Several hundred-million peoples are presently suffering from this disease with other secondary-disorders. Stress, hypertension, sedentary life-style, carbohydrate/lipid metabolic-disorders due to genetic or environmental factors attributes to type-1 and/or type-2 diabetes. Present investigation demonstrates that stress-induced protein dermcidin isoform-2 (DCN-2) which appears in the serum of diabetic-patients play a key-role in this disease pathogenesis/severity. DCN-2 suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…CRP is an acute phase protein and a component of the innate immune system. It is always regarded as a metabolic inflammatory marker ( Wang et al., 2014 ; Bhattacharya et al., 2017 ). DAO is located mainly in the small intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is an acute phase protein and a component of the innate immune system. It is always regarded as a metabolic inflammatory marker ( Wang et al., 2014 ; Bhattacharya et al., 2017 ). DAO is located mainly in the small intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…It has been difficult to determine whether metformin or insulin treatments modulate milk and blood chemistry, including dermcidin concentrations. The concentrations of chemerin (Zhang et al, 2018) and dermcidin (Bhattacharya et al, 2017) are related to insulin resistance. The molecular mechanism of insulin action initiates the activation of kinases to generate a signal that eventually results in insulin’s action on glucose, lipid, and protein metabolism (Ramasarma & Rafi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another molecule, dermcidin, is a peptide consisting of 110 amino acids with antibacterial and antifungal properties (especially protecting against pathogenic gram-positive bacteria) secreted by human eccrine sweat glands (the major sweat glands of the human body that are found in virtually all areas of skin, with the highest density in the palms and soles; Burian & Schittek, 2015; Zeth & Sancho-Vaello, 2017). It has been suggested that dermcidin is part of the innate host defense in the immune system; dermcidin also suppresses pancreatic insulin secretion and increases insulin resistance (Bhattacharya, Khan, Ghosh, Bank, & Maiti, 2017). In a study of patients with diabetes, the detection of dermcidin isoform-2 (DCN-2) in serum ( n = 5 male, n = 15 female) showed that dermcidin plays a key role in the pathogenesis and severity of diabetes (Bhattacharya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T1D is attributed to destruction of the pancreatic β cells or inhibition of glucose uptake [ 12 , 13 ]. T2D is due to pancreatic β cells function decline together with insulin resistance [ 14 ]. Ninety-five percent of diabetic patients suffered from T2D [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%